Viral vaccines and antiviral drugs: report of a WHO scientific group - WHO scientific grop on viral vaccines and antiviral drugs; World health organization (WHO) (Geneva: World health organization, 1983)
In order that the new technologies are harnessed for the maximum benefit of all countries, it is essential that WHO should coordinate the efforts of scientists and others involved in research and development work in this field. Careful consideration should be given to clinical studies of new vaccines and drugs and to their standardization and control. During the past decade, communicable diseases have continued to have a considerable impact on morbidity and mortality, often resulting in an insupportable burden on national health resources. In many areas, viral infections account for a major proportion of the total incidence of communicable disease and, moreover, are often accompanied by secondary bacterial infections. In some countries, effective prevention and control of certain viral diseases, such as measles and poliomyelitis, is adequate using the vaccines currently available. Nevertheless, improvements in the prevention and control
1. Introduction -- 2. Antiviral immune responses -- 3. New approaches to vaccine development -- 4. Developments in interferons and antiviral compounds -- 5. Consideration of specific viral diseases -- 6. Recommendations
Includes bibliography
Keywords: Biological Science; Vaccines and antiviral drugs